2020
DOI: 10.3390/ijerph17093102
|View full text |Cite
|
Sign up to set email alerts
|

Multi-System Physical Exercise Intervention for Fall Prevention and Quality of Life in Pre-Frail Older Adults: A Randomized Controlled Trial

Abstract: Effective interventions for indicated fall prevention are necessary for older adults with frailty. We aimed to determine the effectiveness of a Multi-system Physical Exercise (MPE) for fall prevention and Health-Related Quality of Life (HRQOL) in pre-frail older adults. This randomized control trial with allocation concealment included 72 adults aged 65 and above, identified as pre-frailty and with mild and moderate fall risk scores measured by the Physiological Profile Assessment (PPA). Randomly, using block … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(113 citation statements)
references
References 63 publications
(68 reference statements)
3
107
0
3
Order By: Relevance
“…Moderate to vigorous intensity aerobic exercise could be advocated to the physically independent aged population, and muscle-strengthening for major muscle groups should be done more than twice a week to promote their physical fitness. Furthermore, PA on the basis of multiple components is a viable solution for fall prevention among community-dwelling older adults with prefrailty [ 49 ]. To avoid getting frail in old age, healthy older adults should engage in vigorous and moderate PA while they are non-frail [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moderate to vigorous intensity aerobic exercise could be advocated to the physically independent aged population, and muscle-strengthening for major muscle groups should be done more than twice a week to promote their physical fitness. Furthermore, PA on the basis of multiple components is a viable solution for fall prevention among community-dwelling older adults with prefrailty [ 49 ]. To avoid getting frail in old age, healthy older adults should engage in vigorous and moderate PA while they are non-frail [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 22 selected RCTs provided 10 RCTs for multi-modal exercises [9][10][11][12][13]16,18,21,22,24], 2 RCTs for bi-modal exercises [27,30], 8 RCTs for uni-modal exercises [17,19,20,23,25,26,2829], and 2 RCTs for home exercise program [14,15] to improve the risk of falls. The postural balance training of the selected RCT studies involved multimodal exercises which consisted of the stretching, dynamic and static balancing, resistance exercise, dual task exercise, gait training, proprioception exercises, aerobic exercise, reaction time, and flexibility, stepping, step-up exercises [9][10][11][12][13]16,18,21,22,24]. Bi-modal exercises in the selected RCTs involved aerobic exercise, resistance exercise, balance and strengthening exercise [27,30].…”
Section: Characteristics Of the Selected Rcts Recordsmentioning
confidence: 99%
“…Comparison Outcomes Supplementary therapy study was stretching exercise [22], and one another study was walking program for control group [28]. Flexibility exercise was provided for control group in only one study [11]. Four studies provided the additional therapy for all participants [9,13,14,28].…”
Section: Country Participants * Intervention Intensity Of Exercisesmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that the regular physical activities or fitness exercise are not only beneficial in reducing symptoms such as obesity, cardiovascular disease, cancer, and diabetes (Wang and Zhou, 2013;George and Kristi, 2017;Tang, 2017) but also in reducing anxiety, depression, and negative emotions, as well as enhancing self-esteem and cognitive function (Anthonieta et al, 2016;Chittrakul et al, 2020). However, although regular exercise can bring many benefits to people, excessive sports and physical activity will also induce psychological and physiological problems (Astrid et al, 2014;Badau and Badau, 2018).…”
Section: Introductionmentioning
confidence: 99%